2020
DOI: 10.1556/650.2020.31813
|View full text |Cite
|
Sign up to set email alerts
|

Emelt szintű szervtámogató és életfenntartó kezelések kritikus állapotú COVID–19-fertőzött betegeken

Abstract: Aneszteziológiai és Intenzív Terápiás Klinika, DebrecenA COVID-19-fertőzéses, kritikus állapotba került betegek körében a cardiorespiratoricus rendszer összeomlása a következő mechanizmusok útján történhet: (1) citokinvihar, haemophagocytosis -szeptikus sokk, (2) uralhatatlan hypoxaemia, (3) specifikus szervelégtelenségek, illetve többszervi elégtelenség részjelenségeként. Ebben az összefoglalóban a fenti állapotok ellátásának és megelőzésének jelenleg rendelkezésre álló terápiás opcióit tekintjük át. A szepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
5
0
9
Order By: Relevance
“…In critically ill COVID-19 patients, a cytokine storm, along with unmanageable hypoxemia, can lead to multi-organ failure. 25 The cytokine profile with COVID-19 consists of increased IL-2, IL-7, G-CSF, CXCL10, CCL2, CCL3, and TNF-α, 26 ferritin, IL-1β, S100 proteins, 27 and IL-6. 28 A clinical trial in the United Kingdom published their results while our study was ongoing on the beneficial effect of using of low dose dexamethasone treatment in reducing the 28-day mortality rate by 17%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In critically ill COVID-19 patients, a cytokine storm, along with unmanageable hypoxemia, can lead to multi-organ failure. 25 The cytokine profile with COVID-19 consists of increased IL-2, IL-7, G-CSF, CXCL10, CCL2, CCL3, and TNF-α, 26 ferritin, IL-1β, S100 proteins, 27 and IL-6. 28 A clinical trial in the United Kingdom published their results while our study was ongoing on the beneficial effect of using of low dose dexamethasone treatment in reducing the 28-day mortality rate by 17%.…”
Section: Discussionmentioning
confidence: 99%
“…Meduri et al using an ex vivo model of systemic inflammation reported that naïve peripheral blood leukocytes when exposed to prolonged methylprednisolone treatment of un-resolving ARDS exhibited a progressive increase in cytoplasmic binding of glucocorticoid receptor to NFκB, and a concomitant reduction in NFκB DNA binding and transcription of cytokines such as tumor necrosis factor-α and interleukin-1β. 22,25 A recent unpublished study demonstrates that SARS-CoV-2 proteins interact with lung associated proteins more than other organs. 31 The same study demonstrates that SARS-CoV-2 interacts with multiple innate immune pathways, 31 which suggests that the lung is very susceptible to SARS-CoV-2 and targeting the cytokine storm during COVID-19 and steroid treatment may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…NO inhalation is beneficial for most patients with severe ARDS 240 . Inhalation of NO triggers the relaxation of smooth muscles in pulmonary blood vessels, leading to increased blood flow and adequate ventilation in the lungs 241 . NO showed inhibition of the synthesis of viral RNA and proteins 242 .…”
Section: Small-molecule Sars-cov-2 Inhibitors Targeting Host Proteinsmentioning
confidence: 99%
“…NO showed inhibition of the synthesis of viral RNA and proteins 242 . Therefore, NO inhalation may be an effective method for the treatment of patients with severe COVID-19 169 , 241 .…”
Section: Small-molecule Sars-cov-2 Inhibitors Targeting Host Proteinsmentioning
confidence: 99%
“…По сути, развивается своеобразный «физико-химический пневмонит», который резко утяжеляет состояние пациента и снижает эффективность искусственной вентиляции легких [79,144]. В этом случае более эффективна экстракорпоральная мембранная оксигенация (ЭКМО) крови [67,74], как это рекомендовано для пациентов с ОРДС при тяжелых формах гриппа А [12], дополненная ингаляциями оксида азота [42] и/или Гелиокса [7,97]. Перспективным препаратом для преодоления негативных последствий пневмонита мог бы стать Перфторан [18,25].…”
unclassified